2005
DOI: 10.1007/s11365-005-4776-5
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Strategies in the UK Fashion Industry—The Rhetoric of Partnership and Realities of Power

Abstract: This paper focuses on the fashion industry, one characterised by issues such as dramatic shifts in the scale and power of major retail buyers in the market, the advent of retailer own brands, and the nature of sourcing and supply chain decisions, issues that are increasingly global in nature. The aim of this research is to explore the nature of relationships between UK high street multiple fashion retailers and their contracted suppliers, many of whom are entrepreneurial firms by most definitions of the term. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…In upstream relationships, control information is the basis for value appropriation effects, instead, in downstream relationships a complete "accounting for stable and durable relationships" frame is needed to gain financial value Thus, while suppliers need to foster long-term relationships to exploit relational value opportunities, buyers do not have such a need. This finding is broadly in line with previous studies on buyer-supplier power priorities, which argue that buyers' primary priorities focus on short-term issues, whereas suppliers' priorities focus on long-term profitability [46,144]. This difference could be a source of challenging managerial implications for suppliers because suppliers could accept maintaining asymmetrical value exchanges out of fears of disrupting long-term oriented relationships [46,50,56], leading to feelings of inequity [2].…”
Section: Managerial and Theoretical Implicationssupporting
confidence: 87%
See 1 more Smart Citation
“…In upstream relationships, control information is the basis for value appropriation effects, instead, in downstream relationships a complete "accounting for stable and durable relationships" frame is needed to gain financial value Thus, while suppliers need to foster long-term relationships to exploit relational value opportunities, buyers do not have such a need. This finding is broadly in line with previous studies on buyer-supplier power priorities, which argue that buyers' primary priorities focus on short-term issues, whereas suppliers' priorities focus on long-term profitability [46,144]. This difference could be a source of challenging managerial implications for suppliers because suppliers could accept maintaining asymmetrical value exchanges out of fears of disrupting long-term oriented relationships [46,50,56], leading to feelings of inequity [2].…”
Section: Managerial and Theoretical Implicationssupporting
confidence: 87%
“…However, when upstream relationships are faced (buyer role), timely information is not significant for adding operational value to a firm's offers. In this context, sharing disaggregated cost information with suppliers is the key factor to obtain efficiencies in the production process that relies on more valuable products than competitors, this finding provides support to the argument that buyers are more concerned than suppliers about detailed cost information [66,144] that allows to adjust plans properly [70]. No direct or indirect relational effects on operational value creation are found, thus, the control role of information sharing appears to be the basis of partners' operational benefits.…”
Section: Results Of Value Creation and Capturementioning
confidence: 68%
“…The first stage of the research is reported here, where a series of focussed interview scenarios were conducted over an eighteenth month period. Hines and McGowan (2005) called for research that focussed on the SME supply chain and this study is designed using the principles for qualitative methodologies described by Gabriel and Griffiths, (2004). It supports Fillis (2006) by studying the real SME context rather than theoretical expectations of the same, by getting the SMEs to voice their experiences.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically in the highly competitive mid-market fashion retail sector, the realities of CSR demands may be compromised at the factory level by the need to balance the competing commercial realities of cost and lead time (Plank et al 2012;Hearson, 2009;Barrientos and Smith, 2007). In particular, flexibility and responsiveness must be finely balanced against sourcing cost to achieve success (Hines and McGowan, 2005;Masson et al, 2007).…”
Section: Compromises To Csr In Global Apparel Productionmentioning
confidence: 99%